Mineralogical and Fluid Inclusions Study of Epithermal Type Veins Intruding the Volcanic Rocks of the Kornofolia Area, Evros, NE Greece. - Aravani, Foteini; Papadopoulou, Lambrini; Melfos, Vasileios; Soldatos, Triantafillos; Zorba, Triantafillia; Voudouris, Panagiotis (Bulletin of the Geological Society of Greece, 2019)
The volcanic rocks of Kornofolia area, Evros, host a number of epithermal-type veins. The host rocks are Oligocene calc-alkaline andesites to rhyo-dacites. The andesites form hydrothermal breccias and show hydrothermal alteration. The veins comprise mainly silica polymorphs such as quartz, chalcedony and three types of opal (milky white, transparent and green). Amethyst also forms in veins at the same area. Apart from the silica polymorphs, the veins are accompanied by calcite and zeolites. The main aim of this study is the characterization of the silica polymorphs. Using FT-IR analyses, variations in the crystal structure of the three opals were recognized. The green opal is found to be more amorphous than the other two types. Fluid-inclusion measurements were performed in calcite and were compared with amethyst from previous studies. The Th is between 121-175 °C and the Te between -22.9 and -22.4 °C. The salinities range from 0.9 to 4.5 wt % NaCl equiv.